The Diagnosis of Intrapulmonary Metastasis Multifocal Pulmonary Ground-Glass Nodules Based on Oncogenic Driver Mutation: Two Case Reports and Review of Literature - Liang, Yingkuan; He, Kaiwen; Zhang, Biao; Chen, Ke; Pan, Liangbin; Mao, Guocai; Feng, Yu; Chen, Shaomu; Ma, Haitao (Frontiers in Surgery, 2022)
With the increased use of low-dose computed tomography (LDCT), the detection of multifocal pulmonary ground-glass nodules (GGNs) has increased. According to current clinical guidelines, multifocal GGNs tend to be treated as the multiple primary early-stage lung adenocarcinoma. However, studies have indicated that parts of multiple GGNs may originate from single nodules via intrapulmonary metastasis (IPM). Such IPM indicates the advanced stages even when multiple GGNs are present as early characteristics in pathological assessments. However, no gold standard exists for the differential diagnosis of multiple IPM GGNs. Here, we report two multifocal pulmonary GGNs cases, where panel sequencing (672 driver mutation loci) showed that patient 1 (P1) shared two rare epidermal growth factor receptor (EGFR) mutations (primary L747_T751del and primary T790M) in the left upper lobe anterior segment and left lower lobe superior segment, respectively. Patient 2 (P2) shared a low-frequency human epidermal growth factor receptor 2 (HER2) mutation (primary Tyr772_Ala775dup) in two GGNs located in the apicoposterior and superior lingular segment of the left lower lobe (LLL). Oncogenic driver mutations were concordant between primary tumors and metastasis. Thus, shared low-frequency driver mutations in multiple GGNs strongly suggested that IPM existed with a high probability in these patients. Also, tumor cell spread through air spaces (STAS) was identified in pathological sections of P1’s left upper lobe nodule (LUL), suggesting aerogenous spread may have been an effective pathway for IPM. Our report suggests oncogenic driver mutations have prominent diagnostic value for IPM. Also, GGN IPM may occur in one lung lobe, and between different lung lobes.